Genetic characterization of African chicken using mitochondrial DNA D-loop sequences. - Mobegi, V.A. (University of Nairobi, 2006)
Knowledge of the genetic diversity is a prerequisite for better utilization of any genetic resource. However, such information is lacking for the indigenous African chicken. Mitochondrial DNA (mtDNA) displacement (D)-loop sequences were used to study the genetic diversity, genetic differentiation and phylogenetic relationships between domestic chicken populations and/or breeds of Africa. A total of 398 individuals belonging to 28 populations were sampled from 12 African countries. The hypervariable 1 (HV1) segment of the D-Ioop was peR amplified and subsequently sequenced. The sequences of the first 397 nucleotides were used for analysis. Fifty-two haplotypes were identified from 50 polymorphic sites with polymorphism between nucleotides 167 and 397 contributing to 96% of the sequence variations. Phylogenetic analysis of the haplotypes indicates that African domestic chicken mtDNA can be grouped into six distinct maternal lineages' with one to four lineages observed in each population. One of the haplotypes ;,;- - (represented by Bur60) is shared by alT'populations except Malawi, suggesting that these populations may share the same maternal-;"~ancestor. The phylogenetic relationships between populations show a close relationship between Kenya, Malawi, and three Botswana populations (Malolwane, Semitwe and Motokwe). Genetic variations within populations and between- populations accounts for 64.8% and 35.2% of the total genetic variation, respectively. Network analysis shows a star-like population structure which suggests a rapid population 'expansion from a small number of founding ancestors. These results show a high mitochondrial D-loop diversity in African chicken and indicate multiple maternal origins for African domestic chicken.